STUDIES ON NATURAL PRODUCTS OF ALBIZIA SP. - HILMAN AFFANDI ARIFNURYADIN; HILMAN AFFANDI (BIOTROPIA, 1998)
The bark of  Albizia lebeckioides  and  Albizia falcataria  have been examined for their chemical constituents. A. lebeckioides has yielded the steroidal ketone, stigmasta-4,22-dien-3-one, and a triterpene alcohol as the major neutral components.  A. falcataria  has yielded a similar triterpene  and fatty ester as its major constituents. The toxicity of the compounds was evaluated in bioassay against termites. The results showed that lupenone and stigmastadienone were toxic  ioNeotermes dalbergiae  species. In contrast these compounds were less toxic to Cryptotermes cynocephalus species. Key words: Insecticidal plants / Albizia lebeckioides I Albizia falcataria I Bark / Extracts / Chemical constituents / Toxicity / Termites